Anatomical and correlative biometrical study of head and pituitary gland of Gaddi sheep (Ovis aries) - ARCHANA, ARCHANA; PARAMASIVAN, S; SHARMA, D N (The Indian Journal of Animal Sciences, 2014)
Studies were conducted on 36 heads of adult female pleuriparous Gaddi sheep of 2.5-3,5 years of age. The sheep has long head (cephalic index 66.1) with a prominent nose bridge; the dorsal and ventral length of the head being equal and the cranial cavity almost rectangular and flat. The pituitary was elongated pyriform in shape. Its length, width and thickness were affected by interorbital distance. The skull base length affected length and width while the cranial width affected thickness and width of the pituitary gland. The given regression equation can be utilized to predict the size of the pituitary gland on the basis of known external parameters of head within the safe limits (P<-0.05).